Aplikované aktivity radiofarmak, radiacní zátĕz a radiacní riziko vysetrovacích postupů v nukleární medicínĕ - Husák, V; Petrová, K; Masopust, J; Myslivecek, M (Casopis lekaru ceskych, 1999)
Consistent with the worldwide development of nuclear medicine, in the Czech Republic in 1987 to 1996 partly the spectrum of used radiopharmaceutical preparations and their ratio changed. In the majority of radiopharmaceutical preparations the mean administered activity increased by 20 to 80% and the range of activities administered in different departments diminished somewhat. Adherence to principles of radiation protection of patients is assisted by guidelines of administered activities of radiopharmaceutical preparations laid down in new regulations on radiation protection valid in the CR from the middle of 1997. The radiation burden associated with the majority of examinations in nuclear medicine expressed as the effective dose is comparable with the radiation burden of radiodiagnostic examinations, only after administration of preparations with 131I, 201Tl, 67Ga and 111In it is markedly higher. Based on knowledge of the effective dose it may be concluded that the lifetime extra risk of a fatal tumour due to administration of radiopharmaceutical preparations is by two to three orders lower than the lifetime risk of spontaneous development of fatal tumours. A special feature of radiation risk is its hypothetical character--it is frequently projected into the distant future of human life, contrary to immediate non-radiation risks of some medical procedures and risks in the living environment which frequently are higher. Any examination using ionising radiation can be made only if the expected health benefit for the patient is significantly greater than the radiation risk. Excessive fear of radiation risk should not lead to refusal of justified examinations with possible subsequent serious health damage for the patient.
Keywords: Humans; radiofarmaka; Radiation Protection; rizikové faktory; Radiopharmaceuticals; Czech Republic; Risk Factors; Česká republika; radiační ochrana; lidé; Radiation Dosage; dávka záření